Macroeconomic factors and foreign portfolio investment volatility: A case of South Asian countries - Yahya Waqas; Shujahat Haider Hashmi; Muhammad Imran Nazir (Future Business Journal, 2015)
Macroeconomic factors play a pivotal role in attracting foreign investment in the country. This study investigates the relationship between macroeconomic factors and foreign portfolio investment volatility in South Asian countries. The monthly data is collected for the period ranging from 2000 to 2012 for four Asian countries i.e. China, India, Pakistan and Sri Lanka because monthly data is ideal for measuring portfolio investment volatility. For measuring volatility in foreign portfolio investment, GARCH (1,1) is used because shocks are responded quickly by this model. The results reveal that there exists significant relationship between macroeconomic factors and foreign portfolio investment volatility. Thus, less volatility in international portfolio flows is associated with high interest rate, currency depreciation, foreign direct investment, lower inflation, and higher GDP growth rate of the host country. Thus findings of this study suggest that foreign portfolio investors focus on stable macroeconomic environment of country.
Keywords: 650; Foreign direct investment; Foreign portfolio investment; GARCH model; Macroeconomic factors